Evaluation of Rifampin's Transporter Inhibitory and CYP3A Inductive Effects on the Pharmacokinetics of Venetoclax, a BCL-2 Inhibitor: Results of a Single- and Multiple-Dose Study - Agarwal, Suresh K; Hu, Beibei; Chien, David; Wong, Shekman L; Salem, Ahmed Hamed (Journal of clinical pharmacology, 2016)
Venetoclax is a selective, potent, first-in-class B-cell lymphoma-2 inhibitor that has demonstrated clinical efficacy in a variety of hematological malignancies. A single-dose and multiple-dose rifampin study was conducted to evaluate the effect of CYP3A induction and transporter inhibition on the pharmacokinetics of venetoclax. Subjects received a single dose of venetoclax 200 mg on day 1 of period 1 and days 1 and 14 of period 2, a single dose of rifampin 600 mg on day 1 of period 2, and rifampin 600 mg once daily on days 5 through 17 of period 2. Blood samples were collected up to 96 hours after each venetoclax dose on day 1 of period 1 and days 1 and 14 of period 2. Compared with venetoclax alone, coadministration with a single dose of rifampin increased venetoclax C and AUC by 106% (90%CI, 73%-145%) and 78% (90%CI, 50%-111%), respectively, whereas coadministration with multiple doses of rifampin decreased venetoclax C and AUC by 42% (90%CI, 31%-52%) and 71% (90%CI, 66%-76%), respectively. It was possible to isolate the net effect of chronic CYP3A induction from acute P-glycoprotein (P-gp) inhibition by comparing venetoclax exposures following coadministration with multiple doses of rifampin versus a single dose of rifampin, which showed that CYP3A induction decreased venetoclax C and AUC by 72% and 84%, respectively. These results are consistent with venetoclax being a P-gp substrate and indicate that CYP3A plays a major role in venetoclax metabolism. Prescribers should consider agents with little or no CYP3A induction during treatment with venetoclax.